The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.jadohealth.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Weightism, Racism, Classism, and Sexism: Shared Forms of Harassment in Adolescents

Abstract: Purpose The purpose of this study was to document the prevalence of harassment on the basis of weight, race/ethnicity, and socioeconomic status, as well as sexual harassment, among a diverse population of adolescents. Specifically, this study examined rates of each type of harassment reported across groups within the corresponding sociodemographic category (e.g., racial/ethnic category differences in prevalence of racial harassment), and also explored patterns of “cross-harassment” (i.e., differences in preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
4
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 28 publications
7
111
4
3
Order By: Relevance
“…Previous analyses in this sample have identified that individual weight-related teasing is prevalent (Bucchianeri et al, 2013b) and associated with lower self-esteem, lower body dissatisfaction, and greater depressive symptoms in girls and boys (Bucchianeri et al). We hypothesized that the observation of weight-related teasing, through the transmission of perceived societal weight-related ideals, may have a similar association with adolescent psychosocial health and weight control behaviors.…”
Section: Current Studymentioning
confidence: 88%
“…Previous analyses in this sample have identified that individual weight-related teasing is prevalent (Bucchianeri et al, 2013b) and associated with lower self-esteem, lower body dissatisfaction, and greater depressive symptoms in girls and boys (Bucchianeri et al). We hypothesized that the observation of weight-related teasing, through the transmission of perceived societal weight-related ideals, may have a similar association with adolescent psychosocial health and weight control behaviors.…”
Section: Current Studymentioning
confidence: 88%
“…National estimates indicate that weight discrimination is among the most frequent forms of discrimination reported by adults and is comparable to rates of racial discrimination among women [1]. Among youths, weight stigma is experienced as pervasive bullying and victimization and is reported by youths, teachers, and parents to be one of the most prevalent forms of bullying that youths face at school [2][3][4][5]. In addition to numerous social consequences, economic inequalities, and psychological consequences imposed by weight stigma [6], those who experience weight bias or discrimination may be additionally vulnerable to health risk behaviors and outcomes that can exacerbate poor health and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…13 One study of 1555 high school students found that being overweight was reported to be the primary reason that students observed their peers being teased and bullied at school, 14 and more recent evidence from 2793 adolescents similarly demonstrated that weight-based harassment was the most prevalent form of harassment reported by girls (38 per cent), and the second most common form of harassment among boys (32 per cent). 15 Are overweight and obese students adequately protected from weightbased bullying under existing provisions? There is a clear need to identify productive avenues of intervention in response to weight-based harassment.…”
Section: Introductionmentioning
confidence: 99%